Sup-ADF-style bubble detection methods under test - Verena Monschang; Bernd Wilfling (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
In this paper we analyze the performance of supremum augmented Dickey-Fuller (SADF), generalized SADF (GSADF), and backward SADF (BSADF) tests, as introduced by Phillips et al. (International Economic Review 56:1043-1078, 2015) for detecting and date-stamping financial bubbles. In Monte Carlo simulations, we show that the SADF and GSADF tests may reveal substantial size distortions under typical financial-market characteristics (like the empirically well-documented leverage effect). We consider the rational bubble specification suggested by Rotermann and Wiling (Applied Economics Letters 25:1091-1096, 2018) that is able to generate realistic stock-price dynamics (in terms of level trajectories and volatility paths). Simulating stock-price trajectories that contain these parametric bubbles, we demonstrate that the SADF and GSADF tests can have extremely low power under a wide range of bubble-parameter constellations. In an empirical analysis, we use NASDAQ data covering a time-span of 45 years and find that the outcomes of the bubble date-stamping procedure (based on the BSADF test) are sensitive to the data-frequency chosen by the econometrician.
Keywords: C15; C32; C58; G15; 330; Stock markets; present-value model; rational bubble; explosiveness; SADF and GSADF tests; bubble detection; date-stamping